Intraindividual comparison of hepatocellular carcinoma washout between MRIs with hepatobiliary and extracellular contrast agents - Kim, Yeun Yoon; Kim, Young Kon; Min, Ji Hye; Cha, Dong Ik; Kim, Jong Man; Choi, Gyu Seong; Ahn, Soohyun (Korean Journal of Radiology, 2021)
Objective: To intraindividually compare hepatocellular carcinoma (HCC) washout between MRIs using hepatobiliary agent (HBA) and extracellular agent (ECA). Materials and Methods: This study included 114 prospectively enrolled patients with chronic liver disease (mean age, 55 ± 9 years; 94 men) who underwent both HBA-MRI and ECA-MRI before surgical resection for HCC between November 2016 and May 2019. For 114 HCCs, the lesion-to-liver visual signal intensity ratio (SIR) using a 5-point scale (-2 to +2) was evaluated in each phase. Washout was defined as negative visual SIR with temporal reduction of visual SIR from the arterial phase. Illusional washout (IW) was defined as a visual SIR of 0 with an enhancing capsule. The frequency of washout and MRI sensitivity for HCC using LR-5 or its modifications were compared between HBA-MRI and ECA-MRI. Subgroup analysis was performed according to lesion size (<20 mm or ≥ 20 mm). Results: The frequency of portal venous phase (PP) washout with HBA-MRI was comparable to that of delayed phase (DP) washout with ECA-MRI (77.2% [88/114] vs. 68.4% [78/114]; p = 0.134). The frequencies were also comparable when IW was allowed (79.8% [91/114] for HBA-MRI vs. 81.6% [93/114] for ECA-MRI; p = 0.845). The sensitivities for HCC of LR-5 (using PP or DP washout) were comparable between HBA-MRI and ECA-MRI (78.1% [89/114] vs. 73.7% [84/114]; p = 0.458). In HCCs < 20 mm, the sensitivity of LR-5 was higher on HBA-MRI than on ECA-MRI (70.8% [34/48] vs. 50.0% [24/48]; p = 0.034). The sensitivity was similar to each other if IW was added to LR-5 (72.9% [35/48] for HBA-MRI vs. 70.8% [34/48] for ECA-MRI; p > 0.999). Conclusion: Extracellular phase washout for HCC diagnosis was comparable between MRIs with both contrast agents, except for tumors < 20 mm. Adding IW could improve the sensitivity for HCC on ECA-MRI in tumors < 20 mm.
Keywords: Adult; Aged; Carcinoma, Hepatocellular; Contrast Media; Female; Hepatitis B; Humans; Image Processing, Computer-Assisted; Liver Cirrhosis; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies; Sensitivity and Specificity; Extracellular contrast; Gadoxetic acid; Hepatocellular carcinoma; Magnetic resonance imaging; Washout